Odpowiedzi

Najlepsza Odpowiedź!
2009-12-18T21:57:34+01:00
4(2x+3) - 2(4y-1) = 30
(5x+1/3) - (y- 3/4) = 3

8x + 12 - 8y + 2 = 30
5x + 0,33 - y + 0,75 = 3

8x - 8y = 30 - 2 - 12
5x - y + 1,08 = 3

8x = 8y + 16 / : 8
5x - y = 3 - 1,08

x = y + 2
5 (y + 2) - y = 1,92

x = y +2
5y - y = 1,92 - 10

x = y + 2
4y = - 8,08 /: 4

x = y + 2
y = - 2,02

x = - 2,02 + 2
y = - 2,02

x = 0,02
y = - 2,02

2009-12-18T22:02:12+01:00
4(2x+3)-2(4y-1)=30
(5x+1:3)-(y-3:4)=3

8x+12 -8y+2=30
5x+1/3 -y+3/4 =3

8x-8y=30-14
5x-y=3- 3/4 - 1/3 /*12

8x-8y=16 /:8
60x-12y=36 -9 -4

x-y=2 /*(-12)
60x-12y=23

-12x+12y=-24
60x-12y=23
-------------
48x=-1 /:48
x=-1/48

x-y=2
-1/48 -y=2 /*48
-1-48y=96
-48y=96+1
-48y=97 /:(-48)
y=-97/48